1999
DOI: 10.1002/(sici)1097-0231(19990830)13:16<1663::aid-rcm695>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Energy-resolved mass spectrometry: a comparison of quadrupole cell and cone-voltage collision-induced dissociation

Abstract: Collision-induced dissociation (CID) can be effected in the interface region between atmospheric pressure ionization sources and single quadrupole mass analyzers. By varying the electric field in these cone-voltage CID experiments energy-resolved mass spectra can be obtained leading to breakdown graphs exploring the energy evolution of the fragmentation pathways. The breakdown graphs obtained from these cone-voltage CID studies are very comparable to those obtained by varying the collision energy in the quadru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 29 publications
1
75
0
1
Order By: Relevance
“…It is well known 19,20 that CID can be achieved in this region, so-called cone-voltage CID, and it has been clearly established [21][22][23] that the average energy imparted to the decomposing ions increases as the field in the interface region increases. Indeed, recent work [24][25][26][27] has shown that, by varying this field in steps, energy-resolved mass spectra [28][29][30] comparable to those obtained in variable low-energy CID in quadrupole cells can be obtained. The results of these cone-voltage CID experiments are presented in the following either as CID mass spectra at a set cone voltage or as breakdown graphs expressing the percent of total ion abundance as a function of the cone voltage, a measure of the field in the interface region.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known 19,20 that CID can be achieved in this region, so-called cone-voltage CID, and it has been clearly established [21][22][23] that the average energy imparted to the decomposing ions increases as the field in the interface region increases. Indeed, recent work [24][25][26][27] has shown that, by varying this field in steps, energy-resolved mass spectra [28][29][30] comparable to those obtained in variable low-energy CID in quadrupole cells can be obtained. The results of these cone-voltage CID experiments are presented in the following either as CID mass spectra at a set cone voltage or as breakdown graphs expressing the percent of total ion abundance as a function of the cone voltage, a measure of the field in the interface region.…”
Section: Methodsmentioning
confidence: 99%
“…Breakdown graphs are established tools for the interpretation of CID fragmentation processes. [26,27] They display the percentage of a certain fragment population as a function of the cone voltage and allow the interpretation of the genesis and formation of the respective fragments. For caffeine no fragments could be observed up to 40 V but raising the cone voltage to about 70 V led to fragmentation.…”
Section: Esi-ms Experimentsmentioning
confidence: 99%
“…The breakdown graphs express the relative abundance of fragment ions as a function of the collision energy. [25,26] For example, in the case of tetrapeptide 1A which exhibits helix-turn, the intensity of b n-1 + ion starts increasing from 18 eV and remains constant up to 26 eV, whereas a similar trend is absent for the other peptide 1B (Fig. 3).…”
mentioning
confidence: 90%